2016
DOI: 10.1021/acsnano.6b06584
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy: Programmable Atom Equivalents Versus Atoms

Abstract: The programmability of DNA makes it an attractive structure-directing ligand for the assembly of nanoparticle (NP) superlattices in a manner that mimics many aspects of atomic crystallization. However, the synthesis of multilayer single crystals of defined size remains a challenge. Though previous studies considered lattice mismatch as the major limiting factor for multilayer assembly, thin film growth depends on many interlinked variables. Here, a more comprehensive approach is taken to study fundamental elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 31 publications
0
43
0
1
Order By: Relevance
“…[ 15 ] Although there have been crude early examples of colloidal crystals engineered on substrates, the ability to deliberately control the orientation, shape, and location of each individual crystal has not been realized. [ 15,16 ] Without such capabilities, it is difficult to envision how one could exploit such materials in device fabrication. Therefore, a synthetic approach needs to be developed that allows for such structural control.…”
Section: Figurementioning
confidence: 99%
“…[ 15 ] Although there have been crude early examples of colloidal crystals engineered on substrates, the ability to deliberately control the orientation, shape, and location of each individual crystal has not been realized. [ 15,16 ] Without such capabilities, it is difficult to envision how one could exploit such materials in device fabrication. Therefore, a synthetic approach needs to be developed that allows for such structural control.…”
Section: Figurementioning
confidence: 99%
“…By tailoring the structure of the lithographically defined patterning, monolayers were epitaxially grown to match the {100}, {110}, and {111} crystal planes of a bcc superlattice . Later work demonstrated that subsequent rounds of deposition enabled the synthesis of a multilayer, millimeter‐sized single‐crystal (Figure B) . This proxy platform was then used to investigate the alleviation of strain due to lattice mismatch in the PAE thin films by patterning nanodots with periodicities inconsistent with the equilibrium, bulk PAE lattice parameter .…”
Section: Directly Analogizing Colloidal Pae Assembly To Atomic Crystamentioning
confidence: 99%
“…This work also highlights a conceptual advance in controlling PAE microscale structure through combining top‐down lithographic templating and bottom‐up PAE self‐assembly. With such a template, the overall shape of the crystallite is dictated by a set of arbitrary boundary conditions, and its size is theoretically unlimited beyond the conditions that limit the size of the pattern that can be lithographically fabricated …”
Section: Directly Analogizing Colloidal Pae Assembly To Atomic Crystamentioning
confidence: 99%
See 1 more Smart Citation
“…To integrate colloidal crystals into device structures, a variety of different lithography techniques have been developed, including nanoimprinting, direct‐write 3D printing, and e‐beam lithography (EBL) . Although quite useful for many purposes, nanoimprinting often causes structural deformation, direct write 3D printing is limited with respect to the size and composition of the crystal building blocks and the types of symmetries that can be accessed, and EBL is time‐consuming, labor‐intensive, and difficult to implement over large scales.…”
mentioning
confidence: 99%